Effects of dietary calcium levels and limestone particicle size on the performance, tibia and blood of laying hens - Pelicia, K; Mourao, JLM; Garcia, Edivaldo Antonio [UNESP]; Pinheiro, VMC; Berto, da [UNESP]; Molino, AB [UNESP]; Faitarone, ABG [UNESP]; Vercese, F [UNESP]; Santos, GC; Silva, AP [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2011)
A total of 405 23-week-old ISA® Brown layers were distributed in a completely randomized experimental design in a factorial arrangement with nine treatments consisting of three dietary calcium levels (3.5, 3.75, and 4.5%) and three limestone particle sizes (100% fine limestone (FL), 70% FL + 30% coarse limestone (CL) and 50% (FL) + 50% (CL)), with nine replicates of five birds per cage. The following parameters were evaluated: percentage of lay, defective eggs, egg weight, egg mass, feed intake, feed conversion ratio (per kg eggs and per dozen eggs), and mortality. Dietary Ca levels significantly affected lay, with birds fed diets containing 4.5% calcium producing less eggs as compared to those fed 3.0 and 3.75% Ca. Egg production linearly decreased as dietary Ca levels increased, but blood Ca levels (mg/L) increased in 28-week-old birds. The interaction of dietary Ca levels and limestone particle sizes resulted in a reduction in tibial ash Ca content as dietary Ca levels increased and as fine limestone was replaced by coarse limestone. It is concluded that a dietary Ca level of 3.75% and 100% fine particle limestone are required to maintain adequate egg production and available Ca blood level.
Keywords: Egg production; mineral nutrition; mineral particle size